Adaptability of a nitrogen-fixing strain W12 to the diverse environmental factors - ZHANG Li-mei; FANG Ping; JI Tian-wei (浙江大学学报. 农业与生命科学版)
Effects of diverse environmental factors on the growth and nitrogenase activity of a nitrogenfixing bacteria strain W12 were investigated in our experiment. The results showed that W12 was capable of using various carbon sources, propagated quickly and exhibited quite high nitrogenase activity under a range of temperature, pH and sodium chloride concentration conditions: 15-40 ℃, pH4-8.5, 0.01-1.5% NaCl. Nitrogenase activity could was also detected when W12 was cultured in the media containing 5 mmol/L NH4+. Accordingly, so far as its rapid growth and high nitrogen fixation activity were confident that W12 could easily adapt itself to diverse cultural environmental conditions and thus seems to be a promising inoculant in agricultural production.